2019
DOI: 10.3390/w11081690
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Water Temperature of Polish Rivers and Large-Scale Atmospheric Circulation

Abstract: The objective of the paper consisted in determining the effect of macroscale types of NAO, AO, EA, EAWR, SCAND, and AMO atmospheric circulation on changes in water temperature in Polish rivers. The study has made use of a broad body of hydrometeorological materials covering daily water temperature values for 96 water gauge stations located on 53 rivers and air temperature values for 43 meteorological stations. Percentage shares of positive and negative coefficients of correlation of annual, seasonal, and month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 86 publications
(125 reference statements)
3
20
0
Order By: Relevance
“…In the studied region, in winter, the positive EA/WR produced cold advection from the north and was characterised by a lower air temperature, a lower precipitation level, and stronger atmospheric circulation [45]. In the south-eastern region of Baltic Sea, a positive EA/WR indicated the north-westerly air ow [46], and the EA/WRI negatively correlated with air temperature in spring [47], with lake water temperature in spring-autumn [48], and with precipitation amount in summer [46]. According to our data, during the positive EA/WR phase, a higher mean WS and AP in winter and a lower mean T and a higher mean AP both in spring and summer were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the studied region, in winter, the positive EA/WR produced cold advection from the north and was characterised by a lower air temperature, a lower precipitation level, and stronger atmospheric circulation [45]. In the south-eastern region of Baltic Sea, a positive EA/WR indicated the north-westerly air ow [46], and the EA/WRI negatively correlated with air temperature in spring [47], with lake water temperature in spring-autumn [48], and with precipitation amount in summer [46]. According to our data, during the positive EA/WR phase, a higher mean WS and AP in winter and a lower mean T and a higher mean AP both in spring and summer were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of authors have focused on an assessment of change tendencies at the start and end dates of RI and its duration, which, in light of the recorded increase in TA and TW, usually gives a result pointing to the shortening thereof. Apart from warmer winters, an increase in TA in the autumn and spring periods has also been noticeable, especially during the last twenty years of the 20th century but in recent decades as well [38,39,[69][70][71][72], which delays the date of appearance of IP in rivers and also accelerates their disappearance. Analyses conducted for the last five-to-six decades in Polish rivers [21,22,24,25,31,42,51,64,65,[73][74][75] have confirmed that the duration of IP has been shortened, though their respective change trends have differed along individual river sections.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of circulatory determinants impacting the occurrence of IC in the Noteć River was performed by Graf and Tomczyk [23], while an assessment of the relationship between the TW of Polish rivers and large-scale atmospheric circulation, which was accompanied by the disclosure of TW change patterns in Poland, was carried out by Graf and Wrzesiński [38,39] and Marszelewski and Pius [71,72]. Research conducted by Yoo and D'Odorico [5] in Northern Europe showed that the ice regime of surface waters is connected with changes in the North Atlantic Oscillation (NAO) index, the features of which confirm long-term climate change [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studied region, in winter, the positive EA/WR produced cold advection from the north and was characterised by a lower air temperature, a lower precipitation level, and stronger atmospheric circulation [45]. In the south-eastern region of Baltic Sea, the EA/WRI negatively correlated with air temperature in spring [46], with lake water temperature in spring-autumn [47], and with precipitation amount in summer [45]. According to our data, during the positive EA/WR phase, a higher mean WS and AP in winter and a lower mean T and a higher mean AP both in spring and summer were observed.…”
Section: Discussionmentioning
confidence: 99%